Exploring indicators of natural recovery from alcohol and drug use problems: findings from the life in recovery survey in Flanders - Florian De Meyer; Amine Zerrouk; Clara De Ruysscher; Wouter Vanderplasschen (BMC, 2024)
Abstract Introduction Research has established natural recovery (NR) as an important pathway to substance use recovery. Studies investigating correlates of NR have mainly focused on demographic and substance use variables rather than life circumstances. This study seeks to better understand the phenomenon of natural recovery by (i) validating the international scientific literature concerning demographic and substance use indicators of NR in Flanders and (ii) assessing the additional explanatory power of recovery strengths and barriers during active addiction, controlling for demographic and substance use covariates. Methods A total of 343 persons in recovery from alcohol or drug use problems (≥ 3 months) completed an online cross-sectional survey in Flanders. Participants in NR and in recovery after following treatment were compared using multivariate linear regression models. Reasons for not following treatment were analyzed using inductive thematic analysis. Results Higher education level, lower severity of dependence, and cannabis use as the main problem substance (vs. alcohol) were statistically significant (p < 0.05) correlates of NR. When scores for the number of barriers and strengths associated with active addiction were added, barriers (but not strengths) were significantly associated with NR. When barrier items were individually tested, having untreated emotional or mental health problems, having a driver's license revoked and damaging property were statistically significant correlates. The most reported reason for not entering treatment was not experiencing any need to do so. Conclusion The results highlight the importance of a holistic approach to recovery support across multiple life domains. Limitations and opportunities for further research are discussed.